Mind the Gap: The Relation Between Identity Gaps and Depression Symptoms in Cultural Adaptation - Amado, Selen; Snyder, Hannah R.; Gutchess, Angela (Frontiers in Psychology, 2020)
Personal-enacted identity gaps, defined as the difference between an individual’s self-view and the self that one expresses in communication, affect depression levels of international students living in the United States. Thus, identity gaps are an important construct for understanding the relation between identity and health outcomes. The present research examined the relation between personal-enacted identity gaps formed through communication with Americans and depression, extending previous work by considering the roles of acculturative stress and self-construal and providing one of the first tests of the relation between identity gaps and acculturative stress. A sample of 171 undergraduate and graduate international students studying in the United States was recruited to participate in an online study consisting of self-report questionnaires. Results indicated that as hypothesized, higher levels of personal-enacted identity gaps were associated with depression symptoms and that acculturative stress mediates this relation. However, independent self-construal did not moderate the relation between these variables. Testing additional models revealed multiple ways in which these factors could affect each other. Overall, results suggest that personal-enacted identity gaps, acculturative stress, and depression symptoms are important to consider in tandem in order to understand the emotional experiences of the international students and identify who is at risk for poor mental health. Future longitudinal research is needed to further understand the relations amongst these factors.